Pendampingan Kelompok Tani "Karya Mandiri" di Desa Sukorejo Ponorogo melalui Digitalisasi dan Labelisasi Produk Pertanian - ‘Aris, Muhammad Raffal; Dwicahyo, Agung; Jamil, Muhammad Shobrun; Daniswar, Haidar Aly; Ridho, Muhammad Najib; Sasongko, Yogi banar; Harris, Jaudat Iqbal (Journal Of Human And Education (JAHE), 2025)
The development of digital technology provides great opportunities for the agricultural sector to increase product competitiveness. However, many farmer groups still face obstacles in utilizing digital technology and modern marketing. One group that experiences this challenge is the "Karya Mandiri" farmer group in Sukorejo Village. For this reason, this mentoring program is carried out with the aim of increasing the understanding and skills of farmer group members in the digitalization and labeling of agricultural products in order to increase their selling value and market reach. The methods used in this mentoring include several stages, namely: (1) Identification of needs through an initial survey to determine the level of farmers' understanding of digitalization and product labeling, (2) Digitalization training which includes the use of social media and increasing access to marketing through location registration on Google Maps, (3) Product labeling training to increase the attractiveness of packaging, and (4) Evaluation of the impact of activities through a post-training survey. The results of this activity show an increase in the understanding of farmer group members in the aspects of digitalization and marketing of agricultural products. Before the training, only 40% of participants understood the basics of digitalization, increasing to 85% after the training. The use of social media for marketing increased from 30% to 80%, while the use of social media increased from 30% to 80%. In addition, the farmer group succeeded in creating more attractive product labels, which had an impact on increasing competitiveness in the local market. With this assistance, it is hoped that the "Karya Mandiri" farmer group can independently implement digital-based marketing strategies and more effective product labeling, so as to improve the welfare of its members.